POLITICAL DOWRY: REASONS FOR RESTRICTION, LAW ENFORCEMENT, AND PREVENTIONS - Rajin Sitepu Rajin (Universitas Islam Negeri Antasari Banjarmasin, 2022)
Abstract: The issues related to political dowry are interminable. This interminability is the result of an indication of political dowry every time a general election or local election is held. Based on that background, this article describes the political dowry’s detailed problems. In the beginning, the writer describes the definition of political dowry and its differences from political cost, the reasons for the restrictions, and the law enforcement on political dowry. It ended with some efforts to prevent political dowry. It is found that the definition of political dowry is different from political cost. The regulations restrict the practice of political dowry, but not for the political cost. The political dowry is restricted by law because it is against the national law’s interest, which is the interest to have qualified and fair general elections and local elections. Heretofore, there is no legal punishment for the practice of political dowry due to the difficulty to prove the practice. There are some efforts to prevent the practice of political dowry: First, giving intensive supervision from The General Election Supervisory Agency (Bawaslu) and its subdivisions; Second, revising the regulations in the Law of the Local elections for nominating the candidates; Third, revising the regulations in the law of political parties for nominating the candidates of the president and local government; Fourth, assigning the time limitation for the political parties to accept the political cost; and Fifth, enhancing the legal awareness of all parties involving in the practice of general elections or local elections.Keywords: Political Dowry; Political Cost; General Election; Local Election Abstrak: Isu mengenai mahar politik sepertinya tidak ada habis-habisnya. Isu tersebut menyeruak karena adanya indikasi praktik mahar politik itu terjadi setiap penyelenggaraan pemilu ataupun pilkada. Dilatarbelangi oleh keadaan tersebut, melalui karya ilmiah ini akan digambarkan seluk beluk dari masalah mahar politik tersebut. Pada bagian awal akan menggambarkan pengertian dari mahar politik dan perbedaannya dengan ongkos politik (cost politics), lalu dilanjutkan dengan alasan dilarangnya praktik mahar politik itu, penegakan hukum dalam perkara mahar politik, dan diakhiri dengan upaya untuk mengatasinnya. Dari penelaahan yang dilakukan diketahui bahwa pengertian mahar politik itu tidak sama atau berbeda dengan ongkos politik, yang dilarang dalam legislation adalah praktik mahar politik, ongkos politik tidak dilarang. Alasan praktik mahar politik itu dilarang dalam legislation adalah karena perbuatan itu menyerang kepentingan hukum negara, yakni kepentingan dalam rangka terlaksananya pemilu ataupun pilkada yang adil dan berkualitas. Sejauh ini belum ada penjatuhan pidana terhadap praktik mahar politik, di mana hal tersebut dikarenakan sulitnya membuktikan praktik tersebut. Beberapa upaya yang dapat dilakukan untuk mengatasi praktik mahar politik itu adalah: partama, mengintensifkan pengawasan Bawaslu dan jajarannya; kedua, merevisi aturan tentang pencalonan dalam Undang-Undang Pilkada; ketiga, merevisi aturan tentang rekrutmen pencalonan presiden dan kepala daerah dalam Undang-Undang Partai Politik; keempat, menetapkan batas waktu partai politik boleh menerima ongkos politik; dan kelima, meningkatkan kesadaran hukum semua pihak yang terlibat dalam penyelenggaraan pemilu atau pilkada.Kata kunci: Mahar Politik; Ongkos Politik; Pemilu; Pilkada